The evaluation of locoregional tumoral involvement in the cooccurrence of hashimoto thyroiditis with papillary thyroid cancer: a case controlled study - Shirzad Nasiri; Seyed Mostafa Meshkati Yazd; Mahsa Gholami; Sepehr Shahriarirad; Sina Sharghi; Reza Shahriarirad (BMC Endocrine Disorders, 2023)
Abstract Background Papillary thyroid carcinoma PTC is the most prevalent of all thyroid carcinomas. On the other hand, Hashimoto’s thyroiditis (HT), as part of the spectrum of autoimmune thyroid diseases, is a major cause of thyroid hypofunction worldwide. Several studies have aimed to indicate a possible correlation between PTC and HT over the years. This study aims to investigate the correlation between HT disease and PTC tumor invasion rate. Method In the present cross-sectional study, PTC patients with HT were selected among patients referred to the surgical ward of Shariati hospital from 2016 to 2019 and compared in terms of tumor invasion and central LN dissection. Also, a similar group of PTC patients without HT undergoing total thyroidectomy was selected for comparison. The tumor invasion rate was assessed based on invasion indices obtained from postoperative permanent pathology specimens. These indices included tumor type and size, number of involved LNs, lymphovascular involvement, perineural involvement, thyroid capsule involvement, multifocal or unifocal tumor, extrathyroidal proliferation, marginal status, and necrosis. Data were obtained and compared in the two groups with SPSS version 22.0 software. Results Based on the postoperative pathology reports, 50 (56.2%) PTC patients with Hashimoto thyroiditis were compared against 39 PTC patients without Hashimoto thyroiditis. No significant difference was found between the two groups regarding tumor invasion factors such as multifocality, lymphovascular invasion, marginal invasion, extrathyroidal invasion, capsular invasion, and necrosis. Conclusion HT could not be mentioned as an aggravating factor of PTC invasion based on the invasion factors evaluated in pathology specimens.